1992
DOI: 10.1088/0268-1242/7/8/011
|View full text |Cite
|
Sign up to set email alerts
|

Measured intrinsic defect density throughout the entire band gap at the <100> Si/SiO2interface

Abstract: Conductance-frequency measurements down to temperatures of 100 K have been performed on both p-type and n-type (100) silicon oxidized in dry oxygen at 900 "C. The metal electrode capacitors used were not given a postmetallization anneal in forming gas. This has allowed measurements of the intrinsic density of states, capture cross section. and surface potential fluctuations to within 0.06 eV of the band edges. Two peaks in the defect density at energies of 0.3 eV and 0.85 eV above t h e valence band are clearl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…Werner and Guttler [34] and Osvald and Horvath [31] show that at lower temperatures, the lower barrier patches carry a large fraction of the conduction. Similar results in C-V-T curves have been reported in the literature by Sands et al [35]. They show that the accumulation capacitance decreases with increasing temperature.…”
Section: Resultssupporting
confidence: 91%
“…Werner and Guttler [34] and Osvald and Horvath [31] show that at lower temperatures, the lower barrier patches carry a large fraction of the conduction. Similar results in C-V-T curves have been reported in the literature by Sands et al [35]. They show that the accumulation capacitance decreases with increasing temperature.…”
Section: Resultssupporting
confidence: 91%
“…On the other hand, Aydın et al [40] found that density distribution profile of N ss has U shape behavior. Similar results have been also reported in literature [45,46]. Such behavior of N ss can be attributed to interface state continuum and not with single level states or bands of interfacial states as suggested by Kar and Dahlke [14].…”
Section: à3supporting
confidence: 91%
“…Later, a modification for treating the influence of varying surface potential was suggested by Deuling et al 11 and a large number of applications in using the conductance method have followed. [12][13][14][15][16][17][18][19][20] The basic charge carrier statistics for all these approaches to the conductance method leaned on a treatment by Lehovec. 21 The conductance contribution from the interface states was given by an analytical expression obtained by integration across the thermally accessible energy range around the Fermilevel.…”
Section: Introductionmentioning
confidence: 99%